Buddhism for Development Project (BDP) and Development of Lao Society - Phuthavong, Ven. Ekalad (The Journal of International Association of Buddhist Universities (JIABU), 2018)
The research in this article, which is a qualitative paper in nature, has shown that the aims of social development in Lao Theravada Buddhism are twofold. The primary aim is the improvement of life in the society, protection of human rights, and the preservation of the natural environment. The secondary aim is the personal development of individuals. It has also shown that Buddhism for Development Project is concerned with longer term and sustainable social development in Laos, particularly in the six fi elds of (1) Vipassanā meditation, (2) Dhamma Sanjorn, (3) Community Development, (4) Media and Communications, (5) Training and Curriculum, and (6) Metta-Dhamma. All of the departments in the BDP have functions related to social development in Lao society. The Lao Buddhist Saṅgha performs many roles as it uses Buddhist doctrine for further social development and improvement of the lives of many people in Lao society. Furthermore, according to this study, the members of the Saṅgha also take part in a range of Buddhist ceremonies, lead people of the community in the development of organic agriculture, support and protect the environment, and play various roles in HIV and tuberculosis prevention and treatment activities.